Vpliv velikosti delcev organskih komunalnih odpadkov na proizvodnjo bioplina - Sežun, Mija (Acta agriculturae Slovenica, 2009)
In Slovenia we are facing with municipal waste problems, because their treatment is one of the worst solved goals in environmental protection. Landfilling is the most frequently used practise at the moment, which causes releasing of methane gas into the atmosphere. That's why better solutions are needed. In the present study we determined the potential methane production from organic municipal wastes of different particle size (particle size: >100 mm, 40-100 mm, 10-40 mm and <10 mm). We determined volatile solids (VS), total solids (TS), total organic carbon (TOC), kjeldahl nitrogen (TKN), NH+4 and C/N ratio of the samples. Before and after incubation we determined chemical oxygen demend (COD). Following the biomethane potential test (BMP) we calculated parameters like: methane potential, methane yield and max. velocity of methane production. The results show that the particle size has the strongest influence on metan potential of organic waste and the grinding pretreatment is needed before biogas production process.
Keywords: komunalni odpadki; organski odpadki; varstvo okolja; environmental protection; bioplin; metan; Slovenia; Slovenija